Bystander apathy in cyberbullying: when moral engagement disconnects - Pereira, Nádia (2025)
This study explored how adolescents’ moral beliefs and moral disengagement explain bystander apathy in cyberbullying. Semi-structured interviews with adolescents aged 13 to 20 (n = 100, mage = 15.74, sd = 1.52, 52% boys) were conducted. Results from a thematic analysis indicated four main themes. Theme 1 suggested that although perceived as morally wrong, the severity of cyberbullying was devalued. Theme 2 highlighted a moral conflict between intervening and ignoring. Themes 3 and 4 focused on moral disengagement to justify cyberbullying and bystander apathy. Findings highlight the role of moral beliefs and moral disengagement regarding bystander behavior in cyberbullying.